Pengaruh Kecerdasan Emosional, Self Efficacy, dan Beban Kerja terhadap Kinerja Karyawan Pada Mocca Animation Studio Malang - Muhammad Muhammad; Rois Arifin; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis research aims to analyze the impact of emotional intelligence, self efficacy, and workload on employee performance Mocca Animation Studio Malang. The method used in this study is multiple linear regression analysis. The samples used in this study refer to Sugiyono purposeful sampling technique, that is, the researcher  collect samples when all members off the population are used as samples, and there are 53 respondents in total. The results of this study also show the impact positif of emotional intelligence variables, self efficacy, and workload on employee performance Mocca Animation Studio Malang. Keywords : emotional intelligence, self efficacy, workload, employee performance.